Chemokines in the resolution of inflammation: key players and targets for therapeutic modulation - Oliveira, Vivian Louise Soares; Proost, Paul; Struyf, Sofie (Frontiers in Immunology, 2025)
The resolution of inflammation is an active, tightly regulated process essential for restoring tissue homeostasis after an inflammatory process. While chemokines are classically recognized for their roles in leukocyte recruitment and immune cell positioning during the onset of inflammation, emerging evidence highlights their pivotal functions in orchestrating the resolution phase, as well. The chemokine system contributes to inflammation resolution through several complementary mechanisms, including the depletion of pro-inflammatory chemokines, the generation of autoantibodies, the promotion of neutrophil reverse migration, the recruitment and polarization of pro-resolving immune cells such as macrophages and regulatory T cells, and the induction of tissue repair and disease recovery. Modulating chemokine-receptor interactions, enhancing the activity of pro-resolving chemokines, or blocking detrimental chemokine signaling pathways represent promising strategies for the treatment of excessive inflammation or chronic inflammatory diseases. In addition, modulation of glycosaminoglycan interactions or chemokine-modifying enzymes, might also be useful in this context. In this review, we explore the roles of chemokines in resolution, with a focus on their mechanistic contributions to immune modulation and their potential as therapeutic targets for restoring immune balance.